Modulation of the Host Nuclear Compartment by Trypanosoma cruzi Uncovers Effects on Host Transcription and Splicing Machinery - Gachet-Castro, Camila; Freitas-Castro, Felipe; Gonzáles-Córdova, Raul Alexander; da Fonseca, Carol Kobori; Gomes, Marcelo Damário; Ishikawa-Ankerhold, Hellen Cristina; Baqui, Munira Muhammad Abdel (Frontiers in Cellular and Infection Microbiology, 2021)
Host manipulation is a common strategy for invading pathogens. Trypanosoma cruzi, the causative agent of Chagas Disease, lives intracellularly within host cells. During infection, parasite-associated modifications occur to the host cell metabolism and morphology. However, little is known about the effect of T. cruzi infection on the host cell nucleus and nuclear functionality. Here, we show that T. cruzi can modulate host transcription and splicing machinery in non-professional phagocytic cells during infection. We found that T. cruzi regulates host RNA polymerase II (RNAPII) in a time-dependent manner, resulting in a drastic decrease in RNAPII activity. Furthermore, host cell ribonucleoproteins associated with mRNA transcription (hnRNPA1 and AB2) are downregulated concurrently. We reasoned that T. cruzi may hijack the host U2AF35 auxiliary factor, a key regulator for RNA processing, as a strategy to affect the splicing machinery activities directly. In support of our hypothesis, we carried out in vivo splicing assays using an adenovirus E1A pre-mRNA splicing reporter, showing that intracellular T. cruzi directly modulates the host cells by appropriating U2AF35. For the first time, our results provide evidence of a complex and intimate molecular relationship between T. cruzi and the host cell nucleus during infection.